DAMPAK IMPLEMENTASI ENTERPRISE RESOURCE PLANNING (ERP) YANG DIUKUR DENGAN METODE BALANCED SCORECARD TERHADAP KINERJA MANAJERIAL (STUDI KASUS PADA PERUSAHAAN YANG MENERAPKAN ERP MICROSOFT DYNAMICS AXAPTA DI INDONESIA) - Cisilia Tinny Chandra; Yvonne Augustine (Jurnal Magister Akuntansi Trisakti, 2015)
This study is aimed to measure the success of ERP implementation as part of company’s strategic plan. Successful ERP implementation is reflected in the user satisfaction and overall performance, which should be measured periodically to evaluate the impact of ERP implementation on managerial performance. This research was conducted through a survey by distributing questionnaires to Microsoft Dynamics Axapta ERP users in Indonesia. ERP implementation is measured using Balanced Scorecard method. This model uses four interrelated perspectives, namely Financial perspective, Customer perspective, Internal Business Processes perspective, and Learning and Growth perspective. Result of the survey indicates a relationship between ERP implementation in terms of the four perspectives, affect the Managerial Performance. Thus, it can be concluded that the ERP implementation impact on Managerial Performance.